2018
DOI: 10.1007/s13205-018-1145-y
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate induced toxicity to chickpea plants and stress alleviation by herbicide tolerant phosphate solubilizing Burkholderia cepacia PSBB1 carrying multifarious plant growth promoting activities

Abstract: In this study, strain PSBB1 isolated from rhizosphere was identified as, by 16S rDNA sequence analysis and characterized. Strain PSBB1 tolerated glyphosate up to 3200 μg ml and produced IAA (81.6 μg ml), ACC deaminase (69.3 mg protein h), SA (39.3 μg ml) and 2,3-DHBA (26.6 μg ml), solubilized insoluble P (50.8 μg ml) and secreted 29.4 μg ml exopolysaccharides, which decreased with increasing concentrations of glyphosate. Cell damage following glyphosate application was visible under SEM and CLSM. The phytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 62 publications
(53 reference statements)
3
47
0
Order By: Relevance
“…Hence, release of siderophores under Fe-limited conditions could be useful, as siderophore-producing PGPR isolates may be applied for the bio-management of plant pathogens [ 58 , 59 ]. Production of siderophores by soil microorganisms in stressed environments has previously been reported [ 41 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, release of siderophores under Fe-limited conditions could be useful, as siderophore-producing PGPR isolates may be applied for the bio-management of plant pathogens [ 58 , 59 ]. Production of siderophores by soil microorganisms in stressed environments has previously been reported [ 41 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fungicide-induced changes in integrity of bacterial membrane were assessed using CLSM following the method of Shahid and Khan [ 41 ]. A total of 200 µL fungicide-treated or untreated suspensions of freshly grown bacteria and 10 µL propidium iodide [PI: 50 μg mL −1 prepared in phosphate buffer saline (PBS)] dye was mixed.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar study, a concentration-dependent increase in proline content in various organs of Cicer arietinum plants grown under a herbicide-stressed environment has recently been reported. 44 Since, lipid peroxidation is believed to act as a biomarker for oxidative stress, the assessment of MDA content in plants is inevitable. Malondialdehyde (MDA), synthesized in plants, is a decomposition product of the polyunsaturated fatty acid component of membrane lipid.…”
Section: Seed Germination and Vigour Indexmentioning
confidence: 99%
“…Egamberdieva et al () demonstrated the colonisation potential of P. chlororaphis TSAU13 and P. extremorientalis TSAU20 strains on tomato roots under saline soil conditions. Similar results were also described by Shahid and Khan () and Shankar, Ponraj, Ilakkiam, and Gunasekaran (). It has been reported that the successful rhizosphere colonisation of PGPR is affected by a variety of stressors, such as drought, temperature, salinity and soil type (Compant, Clément, & Sessitsch, ).…”
Section: Discussionmentioning
confidence: 99%